Mandibular trabecular fractal dimension in individuals with type 2 diabetes and hypertension: a retrospective cross-sectional panoramic radiography study - Burak İncebeyaz (BMC Oral Health, 2026)
Abstract Background This study evaluated mandibular trabecular bone microarchitecture in individuals with Type 2 diabetes and hypertension using fractal dimension analysis on panoramic radiographs, comparing findings with healthy controls. Methods This retrospective study included 156 individuals (Control: 43, Hypertension: 63, Diabetes: 50). Fractal dimension was measured on mandibular molar regions using the box-counting algorithm. Age-related confounding effects were adjusted for using Analysis of Covariance. Intra-observer reliability was assessed via Intra-Class Correlation Coefficient. Results Gender distribution was similar across groups, but controls were younger. After statistical age adjustment, systemic diseases impacted fractal dimension values. Age-adjusted fractal dimension averages for the diabetes (1.409) and hypertension (1.407) groups were higher than the control group (1.386). Intra-observer reliability was excellent. Conclusions Type 2 diabetes was significantly associated with higher microarchitectural complexity in mandibular trabecular bone, whereas the increase in the hypertension group did not reach statistical significance. Fractal analysis on routine panoramic radiographs may serve as an adjunctive non-invasive clinical tool to assess these systemic effects, though these preliminary findings require validation with established reference methods.